Effects of a Quality Management System on the Financial Performance in Banking Sector: Case Study Kosovo - Lleshi, Samir; Lirim Lani, (European Journal of Multidisciplinary Studies, 2017)
Creating and improving the services quality, presses the financial institutions to make differentiation from the competition and better position in market for itself. The modern approach to quality management system in the financial and banking sector includes faith, activities which make the client satisfied and this is particularly true in the goodness and help the employees with whom customers will come in contact giving accurate and clear information, discipline and long-term approach. The objective of this study was to establish the effect of quality management system on financial performance in the Kosovo banking sector. At the same time, the concept of quality as a rule leads to confusion and misinterpretation, because it is difficult to determine its exact meaning. The quality of the product or service is the first and often the last thought of the people, when they talk about quality. The concept of quality as an indicator of fulfilling the requirements of the standards or level of excellence is part of advertising, when it comes to their product or service. In tackling the problem, we used empirical methods, which will enable us a correct result of our paper. The results of the paper does not result in significance between banking services and performance of the banking sector in Kosovo.
Keywords: Quality management, financial services, customer, banking sector, quality dimensionsЈЕL Classification:M-10; L-15; G-21 / UDC Classification: 005. 6. 336. 7